Factores socioeconómicos relacionados a la conducta criminal en menores infractores del Ministerio de Justicia Iquitos 2020 - Berrio Paredes, Ccori Stefany (2022)
The thesis entitled: "Socioeconomic factors related to the criminal behavior of minor offenders of the Ministry of Justice Iquitos 2020" had the general objective of determining how socioeconomic factors and criminal behavior are related in minor offenders of the Ministry of Justice in Iquitos, year 2020. To fulfill it, a correlational, observational, analytical, cross-sectional and retrospective study was developed. The design was non-experimental. The population was made up of lawyers and psychologists from the city of Iquitos, whose sample was obtained through non-probabilistic convenience sampling. The techniques used were the survey and content analysis. The applicable instruments were the questionnaire and the Data Recording Form. The results of the investigation determined that there is a positive correlation between the variables socioeconomic factors and criminal behavior in minor offenders of the Ministry of Justice in Iquitos, year 2020. It was concluded that socioeconomic factors influence the criminal behavior of minor offenders of the Ministry of Justice in Iquitos, year 2020. It was recommended that state policies prioritize measures of a preventive and non-reactive nature, applicable to the socioeconomic factors with the most frequent incidence in the criminal behavior of minor offenders of the Ministry of Justice in Iquitos.